Asthma mortality and death certification in Northern Ireland. Issue 2 (February 1994) - Wright, S C; Evans, A E; Sinnamon, D G; MacMahon, J
Abstract : BACKGROUND–Asthma mortality has been rising in many western countries for largely unknown reasons. One cause could be change in certification practice. This study was designed to investigate the accuracy of death certification in Northern Ireland for the years 1981-4 and, in addition, to assess the reliability of trends observed in asthma death registration from 1957 to 1985. METHODS–The following death certificates were obtained for the years 1981-4: those mentioning asthma (all age groups), chronic obstructive airway disease, emphysema, or chronic bronchitis, but only where the decreased was 55 years or less. Information was collected from medical records, questionnaires to the general practitioner, and interviews with a close relative of the decreased. Death as a result of asthma was confirmed or otherwise by a panel and the confirmed deaths were compared with those registered. The numbers of deaths from asthma for the years 1957-85 were obtained from the offices of the Northern Ireland Registrar General. RESULTS–A total of 174 deaths from asthma was identified; 123 (70.7%) had been registered, while the remainder had been coded under another diagnosis. The annual number of confirmed deaths differed little from the figures of the Registrar General. A sharp increase in the annual number of deaths from asthma was observed, beginning in 1977, following a decline in the mid 1970s. CONCLUSIONS–During the years 1981-4 death certification for asthma was found to be inaccurate. The number of false positive registrations was balanced by the number of false negatives, suggesting that the registered totals reflect actual asthma mortality.